REARING OF ’AYU’ LARVAE (PLECOGLOSSUS ALTIVELIS) BY ARTIFICIAL DIETS. I. EFFECTS OF SOME VITAMINS AND ENZYMES SUPPLEMENTS ON GROWTH AND SURVIVAL - Sultana, N; Hossain, M A; Furuichi, M; Yone, Y (Indian Journal of Fisheries, 2011)
Ayu’, Plecoglossus altivelis is the most prized freshwater fish in Japan after eel. However, culture of this species is not wide spread compared to other freshwater or marine fishes. This is probably due to the complex life cycle of this species